Aggregation stability and organic carbon fraction in a soil amended with some plant residues, nanozeolite, and natural zeolite - Milad Mirzaei Aminiyan; Ali Akbar Safari Sinegani; Mohsen Sheklabadi (International Journal of Recycling of Organic Waste in Agriculture)
This research is aimed to study comparison of the effects of applied nanozeolite and zeolite on aggregation and organic carbon (OC) in each aggregate size fraction in treated soil with different levels of some plant residues and incubation for 90 days. The analysis of variance showed that the effects of applied nanozeolite, zeolite, plant residues, and their interaction and incubation times on MWDw and OC in aggregate size fractions were statistically significant. The results showed that MWDw and OC contents in each aggregate size fraction increased with the additions of nanozeolite, zeolite, and plant residues. This study also revealed that nanozeolite and alfalfa straw were more effective for increasing the MWDw and OC contents in aggregate size fractions than zeolite and wheat straw, respectively. In other words, higher percentage nanozeolite, zeolite, and plant residues resulted in increasing the MWDw and OC in aggregate size fractions. The highest amounts of OC were observed in A and B compounds compared with the control and other treatments. However, the comparison of OC contents in all the treatments showed that proportion of nanozeolite for increasing the OC content was greater than that of zeolite. Also the highest OC contents were observed in larger aggregate size fractions. The MWDw and OC contents increased with the increasing days of incubation in treated soil. Thus, it was concluded that compound A can be more effective to improve the soil carbon sequestration.